Digital Communication Through Design: Indonesian Workers' Experiences with Voice Assistants - Revadi, Chindy E; Zikri, Khairullah; Gading, Akbar; Simanjuntak, Monica R. A (CONTENT: Journal of Communication Studies, 2024)
Voice assistants have transformed how people communicate with smart devices, enhancing productivity through AI. This study examined the usability and satisfaction of Indonesian workers when using Google Voice Assistants in Bahasa and English, incorporating industrial design principles. All participants, of working age, regularly used these voice assistants in both languages. Using the System Usability Scale system, they performed practical tasks in real-world conditions. A statistical analysis revealed significant differences in usability and satisfaction between the languages. The findings highlight notable distinctions in the communication experience between Bahasa and English. This research underscores the role of industrial design in refining AI voice assistant interfaces to better facilitate diverse linguistic interactions and optimize user productivity. Keyword: Voice Assistant, design, communication.